Indústria 4.0: percepção de gestores e estudantes universitários das competências necessárias para os colaboradores em meio a quarta revolução industrial - Anunciado, Lucas Vicente (2023)
The industrial revolutions have marked crucial moments in history, driving advances in production and distribution. From the first revolution with the steam engine to Industry 4.0, with IoT, AI and Big Data, each phase has transformed the economy and society. The fourth revolution, with digitalization and connectivity, optimizes production, making it more efficient and personalized. This study sought to answer the basic question: what skills do managers in industry and engineering students think are important for professionals who want to enter the job market in the midst of the fourth industrial revolution? The aim of this study is to analyze the different perspectives between managers and students on the skills needed by employees who wish to work in companies adopting Industry 4.0 concepts. To this end, a survey was carried out among industry managers and university engineering students, using a questionnaire developed by the Human Resources Management Research Group (GRHP) at the Federal Technological University of Paraná, Ponta Grossa campus, in collaboration with other universities. The main skills perceived by managers and students through the instrument were: professional ethics and reliability, emotional intelligence, proactivity and autonomy, ability to comply with decisions made by superiors, self-learning, ability to solve complex problems, working dynamically and mediation in the problem-solving process. The research contributes to understanding the challenges posed by Industry 4.0 and to identifying the different perceptions of the skills needed by employees in this context.